2020
DOI: 10.1101/2020.10.29.357665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The adaptive benefit of evolved increases in hemoglobin-O2affinity is contingent on tissue O2diffusing capacity in high-altitude deer mice

Abstract: Complex organismal traits are often the result of multiple interacting genes and sub-organismal phenotypes, but how these interactions shape the evolutionary trajectories of adaptive traits is poorly understood. We examined how functional interactions between cardiorespiratory traits contribute to adaptive increases in the capacity for aerobic thermogenesis (maximal O2 consumption, V̇O2max, during acute cold exposure) in high-altitude deer mice (Peromyscus maniculatus). We crossed highland and lowland deer mic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 76 publications
2
4
0
Order By: Relevance
“…The effects of genetic variation in α-globin on arterial O 2 saturation were contingent upon acclimation environment, consistent with other recent findings (Wearing et al, 2020). Mice that were homozygous for highland α-globin (α HH ) maintained higher arterial O 2 saturation in hypoxia and had higher Hb-O 2 affinity than lowland homozygous mice (α LL ) when comparisons were made among normoxia-acclimated mice, but these differences were abolished after hypoxia acclimation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The effects of genetic variation in α-globin on arterial O 2 saturation were contingent upon acclimation environment, consistent with other recent findings (Wearing et al, 2020). Mice that were homozygous for highland α-globin (α HH ) maintained higher arterial O 2 saturation in hypoxia and had higher Hb-O 2 affinity than lowland homozygous mice (α LL ) when comparisons were made among normoxia-acclimated mice, but these differences were abolished after hypoxia acclimation.…”
Section: Discussionsupporting
confidence: 91%
“…Red blood cell O 2 affinity (P 50 , the PO 2 at which haemoglobin is 50% saturation with O 2 ) was calculated using Hemox Analytic Software (TCS Scientific). These measurements of blood Hb content, haematocrit, and P 50 have been previously published (Wearing et al, 2020) but are reported again here to provide insight into the measurements of acute hypoxia responses. In addition, the NO metabolites nitrite, S-nitrosothiols (SNO), and iron-nitrosyl and N-nitrosamine derivatives (FeNO + NNO) were measured by reductive chemiluminescence in plasma and red blood cells for a subset of hypoxia-acclimated mice following euthanasia, using a Sievers Nitric Oxide Analyzer (NOA model 280i, Boulder, CO, USA) and previously described protocols (Hansen and Jensen, 2010; Yang et al, 2003).…”
Section: Supplementary Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…1988 ). To examine the physiological mechanisms by which increases in Hb-O 2 affinity affect whole-animal performance capacity in hypoxia, Wearing et al. (2020) created F 2 interpopulation hybrids between highland and lowland deer mice to randomize associations between allelic α- and β-globin variants on an admixed genetic background.…”
Section: Genetic Experiments Provide Insights Into Mechanism and Process In Hypoxia Adaptationmentioning
confidence: 99%
“…2017 , 2020 ). However, experimental results and mathematical modeling indicate that the increased arterial O 2 saturation only translates into an enhancement of hypoxic V O 2 max when accompanied by a corresponding increase in tissue O 2 diffusion capacity ( Wearing et al. 2020 ).…”
Section: Genetic Experiments Provide Insights Into Mechanism and Process In Hypoxia Adaptationmentioning
confidence: 99%